The Enzymatic Release of O(6)-methylguanine and 3-methyladenine from DNA Reacted with the Carcinogen N-methyl-N-nitrosourea - Kirtikar, D. M. (1974)
Endonuclease II (deoxyribonucleate oligonucleotidohydrolase, EC 3.1.4.30) of Escherichia coli has been shown to break phosphodiester bonds in alkylated DNA and depurinated DNA. The hypothesis that depurination is a step in the mechanism of the reaction with alkylated DNA is supported by in vitro experiments with DNA reacted with N-methyl-N-nitrosourea. Endonuclease II releases O(6)-methylguanine and 3-methyladenine, but not 7-methylguanine, from DNA that has been methylated by the carcinogen N-methyl-N-nitrosourea.